Stress and anxiety in schools: a multilevel analysis of individual and class-level effects of achievement and competitiveness - Becker, Saskia Jasmin; Börnert-Ringleb, Moritz (Frontiers in Education, 2025)
Stress and anxiety are commonly experienced by students in schools. Both phenomena are mutually dependent and associated with various negative outcomes. A range of variables have been addressed when explaining the development of stress and anxiety and the need to consider classroom-level effects becomes clear. So far, the effects of individual as well as classroom-level competitiveness on stress and anxiety have not been focused. This study aims to address this research gap and examines associations between achievement, competitiveness, stress and anxiety. Therefore, cross-sectional self-reports of 591 students from 10 secondary schools in Germany were collected using a paper-pencil-questionnaire in regular classrooms and analyzed using hierarchical linear modeling. The results highlight the relevance of achievement and competitiveness for the experience of anxiety and stress of students. Academic achievement on individual and class level were related to individual and classroom levels of stress and anxiety. Similarly, competitiveness on both levels was positively associated with the experiences of stress and anxiety. Consequently, the study highlights the relevance of achievement and competitiveness for the experience of anxiety and stress of students and emphasizes a need for adequate educational support.